2010
DOI: 10.1007/s00198-009-1121-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bone mineral density of the lumbar spine and prevalent vertebral fractures on the risk of immobility

Abstract: These results indicate that low BMD and prevalent vertebral fracture pose an independent risk for future immobilization in postmenopausal Japanese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Osteolytic bone diseases such as osteoporosis, rheumatoid arthritis, and periodontitis are becoming more and more serious medical problems as the populations in industrialized countries rapidly age [Cochran, ; Shiraki et al, ; Schett and Gravallese, ]. These disorders markedly reduce quality of life (QOL) and ability of daily living (ADL) of the patients, while significantly increasing medical and caring expenses.…”
mentioning
confidence: 99%
“…Osteolytic bone diseases such as osteoporosis, rheumatoid arthritis, and periodontitis are becoming more and more serious medical problems as the populations in industrialized countries rapidly age [Cochran, ; Shiraki et al, ; Schett and Gravallese, ]. These disorders markedly reduce quality of life (QOL) and ability of daily living (ADL) of the patients, while significantly increasing medical and caring expenses.…”
mentioning
confidence: 99%
“…Together with our recent report that showed that osteoporosis is a significant independent risk factor for immobility in Japanese women (31), osteoporosis should be recognized as a harmful disease which may affect the patient's prognosis.…”
Section: Discussionmentioning
confidence: 68%
“…However, serum markers for bone remodeling are usually decreased in patients with GH deficiency [15] whereas our patient showed increased turnover of bone metabolism. Otherwise, immobility can also negatively affect a patient's BMD [16]. It is also possible that TSH deficiency as well as hypothyroidism might affect the reduced BMD in our patient.…”
Section: Discussionmentioning
confidence: 87%